The concept of «Mangilik El» (Journal of Oriental Studies, 2019)
The article gives an indication of an ancient civilization idea of “Mangilik el”, the word “country”. The word “Mangilik el” has a deep historical root and meaning. The word “Mangilik” in the Turkish writing monuments has been used with the words “Tengri”, “God”. After that, “Mangilik el” means “Country and people of Allah Taala”, and there is every reason to believe that the state and the nation are an immeasurable amulet. In the process of reviewing, analyzing, and analyzing national and universal values, recognition of their diversity, the emergence of a new form and a distinctive character will undoubtedly enhance the national outlook. This issue develops public consciousness; these issues are analyzed in detail in this scientific article. Key words: «Mangilik El», great steppe, country, Kultegin’s inscription.